All the Faces of Grochowiak: (J. Łukasiewicz, "Poeta Grochowiak" Wrocław: Warstwy, 2019) - Juchniewicz, Andrzej (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The hereby reviewed book by Jacek Łukasiewicz entitled Poeta Grochowiak has been an impressive and monumental undertaking, yet it fulfils only some of the promises made by its author. According to the reviewer, the fact of its release offers grounds for a discussion of the status of theory and the validity of abandoning it in favour of a reading devoid of methodological regime which elevates the importance of pleasure. The main problem which emerges after reading Łukasiewicz’s opus magnum is the issue of selecting the recipient of the monograph (a regular person or a specialist), which in turn conditions the mode of study of the poet’s output. Łukasiewicz’s monograph amplifies the conviction that Grochowiak’s poetic works should be read using new methodologies, which could indicate the poet’s innovation in terms of increasing the value of objects and animals as the most important components of his universe. According to the reviewer, what requires justification the most is the need to comment on nearly all poems from the poet’s released collections, which is supposed to be facilitated by the researcher’s identification of several categories around which his narration centred. The book was divided into two parts. The first part is predominantly chronological, while the second part follows a contextual organisation, which considering the book’s size causes problems in the form of repeated discussions of several poems. The reviewer noted the fact that some were subjected to careful reading several times while other, especially those not released, did not receive a sufficient amount of attention. Additionally, Łukasiewicz did not attempt to define the gravity of the topic of the most recent world war in Grochowiak’s output or to reconstruct the poet’s polemic with Julian Przyboś during the mature stage of the former’s creative life. An in-depth analysis is also demanded for poems discussing the suffering of animals and inter-species community, which Łukasiewicz deemed noteworthy yet his comments to those do not help readers find indications of eco-critical awareness in Grochowiak’s works. The new monograph devoted to the output of the author of Kanon sheds new light on many problems and biographical contexts as the critic knew the poet, yet some issues require further study. Poeta Grochowiak as the crowning of Łukasiewicz’s efforts into the study of the poet’s output is impressive, yet there is no doubt that a panoramic view does not guarantee noticing every detail, and it is in details that Grochowiak’s poetic sensitivity is lodged.